PEMAHAMAN PEMILIH PEMULA TERHADAP MONEY POLITIC MENJELANG PEMILU 2024 PADA MAHASISWA PPKn UNIMED STAMBUK 2023 - Damanik, Indah Puja Claudia; Bangun, Jacklyn Alona; Putra, Bayu Ardiansyah; Boangmanalu, Vivin Silvia; Bangun, Kezia Thasa Emteta Karina; Ivanna, Julia (Jurnal Sosial Humaniora Sigli, 2023)
Ahead of elections and regional elections, of course, the rise of money politics is a challenge for the community, including novice voters. This can certainly threaten and damage the integrity of voters and hurt democracy in Indonesia. This research was conducted to review the understanding of Medan State University students, majoring in Pancasila and Citizenship Education Stambuk 2023 as novice voters regarding money politics and its impact on democracy in Indonesia. This research was conducted using a descriptive qualitative method of conducting interviews with PPKn Stambuk 2023 students related to how much their level of understanding about money politics ahead of the 2024 election. This research found that the understanding of PPKn FIS UNIMED Stambuk 2023 students regarding money politics is strong enough that it is hoped that ahead of the 2024 democracy party, students will be able to take a bold stance to reject the practice of money politics and uphold the principles of an honest and fair electoral system in order to realize Indonesia free from political corruption.Keywords: Comprehension, Novice Voters, Political Money, Elections